Environment, Social and Governance Reporting and Firm Performance: Evidence from GCC Countries - Sharma, Raj Bahadur; Lodha, Shilpa; Sharma, Asha; Ali, Sajid; Elmezughi, Abdalla Mohamed (International Journal of Innovative Research and Scientific Studies, 2022)
The aim of this research is to investigate the impact of ESG reporting on firm performance, Environment, Social and Governance (ESG) are a triple-bottom-line approach that combines financial gains with adhering to social, governance and environmental norms. In addition, the study's objective is to determine the relationship between ESG disclosure and firm performance in Gulf Cooperation Council (GCC) listed companies. ESG scores and other samples for 91 firms from 6 GCC countries were collected for this purpose over a three-year period from 2019, 2020 and 2021. The sample comprised nine diverse industries. The dependent variables are Return on Assets (ROA) and market capitalization , experimental variables are environmental pillar score, social pillar score, governance pillar score and overall ESG score and the control variables: size, leverage. The study found that ESG scores and governance pillar scores have a positive impact on a firm’s market value but environmental and social pillar scores were not significant. In addition, there is a strong relationship between all ESG disclosures and ECG scores.